Odpowiedzi

2010-03-09T06:34:19+01:00
A)

3(x-2)-x=5x+2
3x-6-x=5x+2
2x-6=5x+2
-6-2=5x-2x
-4=3x /:3
x=3/4

b)
1/2x+4(x-2)=x
1/2x +4x-8=x
1/2 x + 4x - x = 8
5/2x = 8 / * 2
5x=16 /:5
x=3 i 1/5

c)
2x-3=5(x+2)-1
2x-3=5x+10-1
-3-9=5x-2x
-12=3x / :3
x= ( - 4 )

d)
2/3x+1/2=1/6-x
2/3x + x = 1/6 - 1/2
1 i 2/3x = 1/6 - 3/6
1 i 2/3x = - 1/3 / *3
5x=1 / :5
x= 1/5

Liczę na naj.;)
2010-03-09T06:47:29+01:00
A) 3(x-2)-x=5x+2
3x-6-x=5x+2
2x-5x=2=2+6
-3x=8/:(-3)
x~2,66

b) 1/2x+4(x-2)=x
4 1/2x-x=8
3 1/2x=8/:(31/2)
x~2,28

c) 2x-3=5(x+2)-1
2x-3=5x+10-1
2x-3=5x+9
2x-5x=9+3
-3x=12/:(-3)
x=-4

d) 2/3x+1/2=1/6-x
2/3x+x=1/6-1/2
1 2/3x=1/6-3/6
1 2/3x=-2/6
5/3x=-2/6
10/6x=-2/6
x~0,2